Ultimate bearing capacity of CHS X-joints stiffened with external ring stiffeners and gusset plates subjected to brace compression. (15th February 2019) - Chen, Yong; Hu, Zhongzheng; Guo, Yong; Wang, Jiyang; Dan, Hanbo; Liu, Qingsong; Pan, Yu
Highlights: An innovative stiffened X-joints with good performance in tubular structures. 15 specimens are experimentally studied with corresponding numerical verification. Parametric study via finite element analysis reveals essential mechanical mechanism. Strength prediction equations are concluded with corresponding boundary conditions. Abstract: An innovative stiffened circular hollow section (CHS) X-joint is introduced herein, which has been used in offshore long-span transmission towers due to its higher bearing capacity in comparison with traditional CHS X-joint. A total of 15 specimens are employed for the experimental study to gain insight into its mechanical characteristics. Corresponding finite element (FE) analysis is thus conducted. The numerical results are compared with that by tests, and a good agreement is found, which verifies the validity of the setup in the finite element modelling and analysis. By using the settings, a total of 480 joints are numerically modelled and corresponding load-displacement curves and ultimate bearing capacities are obtained by FE analysis. Parametric sensitive study results show that the bearing capacities of corresponding unstiffened X-joint and chord rings could be used for predicting the strength of stiffened X-joints. The predicted results are shown to be in good agreement with that from numerical and experimental studies, and the equations proposed for prediction are applicable for a wide range of joint parameters. In this survey, the stiffened joint is observed to provide strength enhancement up to 811% in comparison with the traditional unstiffened X-joint, which proves that the stiffening method employed herein is capable of improving the bearing capacity greatly.